LITERASI DIGITAL DALAM PENGELOLAAN MEDIA SOSIAL DI TINGKAT KELURAHAN KOTA BANDUNG DAN KOTA BOGOR - Arina Rubyasih; Rachmawati Windyaningrum; Stefani Made Ayu Artharini Koesanto (Jurusan Ilmu Komunikasi Universitas Andalas, 2022)
Digital literacy involved in social media management in government is unique and become something important for communicating within the community. With proper management of social media, information about government programs can be disseminated effectively and efficiently and can be directly responded to by the community as social media users. The formulation of the problem in this study is how to manage digital literacy in social media in Lebak Siliwangi and Cimahpar villages. The two urban villages were chosen for consideration as winners of the 2019 West Java Public Relations Cup, and have renewable social media activities. The results of the study concluded that the digital competence of social media managers in the Siliwangi and Cimahpar urban villages was considered sufficient, however, the level of competence was not at the professional level. The ability of social media management officers in the Siliwangi and Cimahpar urban villages is considered sufficient to be able to access and post information to residents. The desire to adopt content processing capabilities does exist but there are limited human resources. In disseminating information, officers are very careful disseminating information, by reconfirming the information to be posted to avoid misinformation.